Assessing the acceptability of community pharmacy based pharmaceutical care services in Karachi - Muhammad Amir, B.Pharmacy, MSc. MBA, Assistant Professor/Clinical Pharmacist (University of Minnesota Libraries Publishing, 2011)
Provision of pharmaceutical care services in community pharmacies is a new trend in pharmacy practice worldwide. Published literature from developed countries is available showing benefits of pharmaceutical care services provided in community pharmacies. However, relatively little published literature is available from developing countries in which unique market environments are encountered. This study was conducted to assess the acceptability of community pharmacy based pharmaceutical care services in Karachi. Pharmaceutical care services were developed and offered to pharmacy customers for a period of two months. Acceptability was evaluated with respect to enrollment of participants in the program, discontinuation, and complaints registered. The findings provide a better understanding of pharmaceutical care marketing strategies and are discussed within the context of the health care environment in Karachi.